The Impact of EU Programmes on Financing Higher Education Institutions in Western Balkans – Evidence from Kosovo - Jusufi, Gezim; Ajdarpasic, Suada (LeXonomica, 2020)
The main goal of this paper is to analyse the financial effects of EU education and research programs on the development of higher education institutions in Western Balkan countries with a special emphasis given to Kosovo. To achieve the set goal, we have used the integrative review method. The Western Balkan HEIs do not have sufficient financial capacity to develop new curricula, new study programmes and research projects. They must therefore make use of EU education and research programmes to cover this gap. The evidence provided in the paper supports the idea that HEIs of the countries with low economic development, political challenges and lack of institutional capabilities will have a difficult time funding such undertakings without the assistance of EU programmes. Thus, these programs have a great impact on financing these educational institutions effectively. Therefore, their impact on the funding of universities in this region should be elaborated. It should be noted that there is little research which elaborate the impact of these programs on funding Western Balkan HEIs. These are key findings of the paper.